Synthesis And Characterization Of Some New Metal Complexes Of Ethyl Cyano (2-Methyl Carboxylate Phenyl Azo Acetate) - Sarhan, B. M.; Rumez, R. M.; Hassan, H. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Complexes  of  (Co2+, Ni2+, Cu2+, Zn2+, Cd2+ and Hg2+)  with  the  ligand  Ethyl  cyano  (2methyl  carboxylate phenyl  azo  acetate)  (ECA)  have  been  prepared  and characterized  by FTIR, (UV-Visible), Atomic  absorption spectroscopy, Molar conductivity measurements and magnetic moments measurements. The following general formula has been suggested for  the prepared  complexes  [M(ECA)2]Cl2 where M = (Co2+, Ni2+, Cu2+ ,Zn2+, Cd2+, Hg2+) and the geometry is octahedral.